Age Variation in Mating Strategies and Mate Preferences Among College Students - Ryan, Danielle (My University, 2012)
Past research has documented systematic similarities and differences in men's and women's mate preferences and mating orientation. However, one area of mating research that relationship scientists know little about is change over time in individuals' mating orientations and preferences. To address this knowledge gap, this study involved surveying broad samples of students at the University of Wisconsin--Eau Claire.
Color poster with text, graphs, and tables.
Keywords: Courtship; Mate selection--Research; College students--Wisconsin--Eau Claire--Attitudes--Surveys; Posters